FEM simulations for the micro-cracked interfaces - Wang, Bryan Wei En (Nanyang Technological University, 2024)
This paper delves into the intricate world of micro-cracks, particularly those nestled within the interface of two materials. Micro-cracks are indeed pervasive, lurking within solids and components, and they pose a significant threat to structural integrity. What makes this study unique is its focus on zooming in on a single micro-crack along the interface, unraveling the complex interplay between crack development, growth, and their impact on the joint's stiffness and structural cohesion.